-3(4+3)=2y+3

Simple and best practice solution for -3(4+3)=2y+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(4+3)=2y+3 equation:


Simplifying
-3(4 + 3) = 2y + 3

Combine like terms: 4 + 3 = 7
-3(7) = 2y + 3

Multiply -3 * 7
-21 = 2y + 3

Reorder the terms:
-21 = 3 + 2y

Solving
-21 = 3 + 2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2y' to each side of the equation.
-21 + -2y = 3 + 2y + -2y

Combine like terms: 2y + -2y = 0
-21 + -2y = 3 + 0
-21 + -2y = 3

Add '21' to each side of the equation.
-21 + 21 + -2y = 3 + 21

Combine like terms: -21 + 21 = 0
0 + -2y = 3 + 21
-2y = 3 + 21

Combine like terms: 3 + 21 = 24
-2y = 24

Divide each side by '-2'.
y = -12

Simplifying
y = -12

See similar equations:

| 17-3=4x | | -3(q-7)=2+q-21 | | 2x+1=2(x-4) | | 3x^5/6-16=80 | | 2x+1=2(x-8) | | x-5+4x+x+x-8=360 | | 3x-7(x+6)=14 | | 2/3x=1=-1/3x-1 | | 20(-9+6)=-6(x-2) | | 4(3-z)-36=26z-6(4+5z) | | y=c(x-2) | | 4sin^2x+11sinx-3=0 | | 4(3+x)=-4-x | | 1/2(2p-12)=10p | | 12+3x=1.2-4x | | 12+3x=1.24x | | 1n-4=3n+6 | | x+100=3x+50 | | 3(a-3)+6=12 | | y=1/-1/4 | | (.33333)d-5=81 | | -d+5=4 | | -12-5[6-(2*6)]=18 | | 16x^4-7x^2-18=0 | | (1/3)d-5=81 | | -1n+-2+6=-9+8n+4 | | 6y-5=-2x+11 | | 3r+10-6r-4=5 | | 3r+10-6t-4=5 | | 80-10k=4k | | .75=-3 | | 3-4[5-(8y-3)]= |

Equations solver categories